Estimation of effectiveness of usage of liquid organic fertilizer in the context of rational land use: a case study of Ukraine - Kucher, Anatoliy (Przegląd Wschodnioeuropejski, 2018)
The purpose of the article – to perform comparative analysis of the economic effectiveness of the 10 samples of organic fertilizer of pig farm, bio humus “Humivit” and mineral fertilizers (Nitroamofoska, ammonium nitrate, carbamide) on the example of oats. The study used the following methods: abstract-logical, cash-analytical, cash-equivalent, expert, monographic. The research was done in Ukraine. The results of the comparative analysis of economic effectiveness of the 10 samples of organic pig fertilizer, bio humus “Humivit” and mineral fertilizers (Nitroamofoska, ammonium nitrate, carbamide) in the example of oats on the green mass show that the use of organic fertilizers sample number 1, 2, 3, 4, 5, 6, 10 is an economically effective, while organic fertilizers of sample number 7, 8, 9 are economically inefficient. By the main indicators of economic effectiveness (coefficients of payback, conditional additional profit, level of profitability) organic fertilizers sample number 1, 2, 3, 4, 5, 6, 10 have significant competitive advantages over the studied brands of mineral fertilizers and bio humus “Humivit”. The use of organic pig fertilizers, except the sample number 8, in economic terms for the impact on potential soil fertility is more effective than bio humus “Humivit”. The most significant economic benefits for the impact on potential soil fertility are samples of organic fertilizers pig number 1, 5, 10, whose application generates the lowest cost price of humus. The element of novelty is that with using the author’s scientific and methodical approach it was conducted the estimation of economic effectiveness of the liquid organic fertilizer of pig farm for the impact on potential soil fertility.